Anaplasma phagocytophilum in domestic cats from Germany, Austria and Switzerland and clinical/laboratory findings in 18 PCR-positive cats (2008–2020). Issue 4 (April 2022) - Schäfer, Ingo; Kohn, Barbara; Müller, Elisabeth
Objectives: Anaplasma phagocytophilum is considered the most significant rickettsial pathogen affecting cats. The organism is transmitted by ticks of the species Ixodes ricinus in Central Europe and can cause granulocytic anaplasmosis in pets, wildlife and humans. The aims of this study were to assess the frequency of positive test results for A phagocytophilum in cats in Germany, Austria and Switzerland, as well as to evaluate clinical and laboratory findings in cats with positive PCR results. Methods: This study included the results of direct (PCR) and indirect detection methods (immunofluorescence antibody tests [IFAT]) requested by veterinarians in Germany, Austria and Switzerland between 2008 and 2020 from the LABOKLIN laboratory (Bad Kissingen, Germany). The veterinarians treating the PCR-positive cats were contacted by telephone to enquire about their clinical signs, laboratory findings, management and outcomes. Results: In total, 244/1636 cats (15%) tested positive by direct (PCR: n = 27/725 [4%]) and/or indirect detection methods (IFAT: n = 221/956 [23%]). In 18/26 cats with PCR results positive for A phagocytophilum, additional information about clinical signs, laboratory findings, treatment and outcome was obtained. Of these 18 cats, five had comorbidities independent of their infection with A phagocytophilum . The most common clinical signs in PCR-positive cats (total/without comorbidities) were lethargy (83%/92%), fever (83%/85%) and thrombocytopenia (61%/62%). Overall, more than half (57%) of the cats with and without comorbidities recovered clinically. Conclusions and relevance: Infections with A phagocytophilum should be considered as differential diagnoses in cats with tick infestation, lethargy, fever and thrombocytopenia. The clinical signs and laboratory findings are consistent with published case reports in cats. Ectoparasite prophylaxis in cats is recommended throughout the entire year.